Autonomous vehicles, Competence and Liability in the EU : Answering the Call of the European Parliament - Kiilunen, Vilma (fi=Turun yliopisto|en=University of Turku|, 2018)
Technology is taking immense steps in a short period of time and legislators are trying to keep up. Fully autonomous vehicles where human drivers are obsolete are not far away from becoming a reality. The EU aims at facilitating robotic advancements into legislation with the Proposition on Civil Law Rules on Robotics (205/2013(INL)). Consumer protection, market access and liability issues are of main importance concerning driverless vehicles. The main goal of this master’s thesis is to examine autonomous vehicles, competence and liability issues in the European Union context. In other words this thesis examines whether it is possible to regulate on autonomous vehicles on an EU level and if so, what the legislator must take into consideration when doing so or whether current legislation sufficient enough to grant protection for victims of traffic accidents involving autonomous vehicles. The scope of the study is set on future insurance policies, product liability and current national legislation with reference to international policies and regulation. Different legislations on civil liability create a mixed and uncertain background for autonomous vehicles. A uniform and clear EU policy on autonomous vehicles would benefit consumers and market access of said products. The problems can be dissolved with creating an EU wide legal background for autonomous vehicles with product liability, insurance policies and a legal liability theorem. The private sector – the manufacturers and insurance industry – must have an active part in creating legislation and soft law policies. The thesis has achieved its goal if it creates discussion on the importance of harnessing new technology, especially autonomous vehicles. Itseohjautuvat Autot, Kompetenssi ja Vastuuoppi Euroopan Unionissa : Vastaus Euroopan Parlamentille Teknologia kehittyy hurjaa vauhtia ja lainsäätäjillä riittää työsarkaa pysyäkseen sen mukana. Itseohjautuvat autot, jotka ajavat ilman ihmiskuskeja tai -kontrollia, eivät ole kaukana todellisuudesta. Euroopan Unionin tavoitteena on fasilitoida robottiteknologia lainsäädäntöön: Euroopan Parlamentti on päätöslauselmaehdotuksessaan esittänyt suosituksista komissiolle robotiikkaa koskevista yksityisoikeudellisista säännöistä (2015/2103(INL)). Kuluttajansuoja, tavaroiden esteetön pääsy markkinoille ja vastuu kysymykset ovat tärkeitä koskien itseohjautuvia autoja. Tämän pro gradu –tutkielman päämääränä on tutkia itseohjautuvia autoja, kompetenssia sekä vastuu kysymyksiä Euroopan Unionin kontekstissa. Toisin sanoen, tämä tutkielma tutkii mikäli on mahdollista säätää itseohjautuvista autoista EU tasolla, mitä lainsäätäjän tulee ottaa niitä säätäessään huomioon sekä onko nykyinen EU tasoinen lainsäädäntö riittävä suojaamaan uhrien oikeuksia rajat ylittävissä auto-onnettomuuksissa. Tutkielma keskittyy vakuutuksiin, tuotevastuuseen sekä nykyisiin kansallisiin ja kansainvälisiin säädöksiin. Jäsenvaltioiden erilaiset oikeusjärjestelmät koskien siviilioikeutta muodostavat sekavan ja epävarman taustan nykyisellään itseohjautuville autoille, varsinkin rajat ylittävissä onnettomuuksissa. Yhtenäinen ja selkeä EU poliittinen ratkaisu helpottaisi itseohjautuvien autojen käyttöönottoa sekä hyödyttäisi kuluttajia. Ongelmat voidaan ratkaista EU oikeudellisella vastuuopilla ja lainsäädännöllä, joka kohdistettaisiin itseohjautuviin autoihin. Yksityinellä sektorila – nimenomaan autojen valmistajilla ja vakuutusteollisuudella – on oltava rooli lainsäädännön kehittämisessä. Tämä tutkielma on saavuttanut päämääränsä, mikäli se saa aikaan keskustelua uuden teknologian ja lainsäädännön välillä, erityisesti koskien itseohjautuvia autoja.